POLICY AND REALITY: A DESCRIPTIVE ANALYSIS OF TOLERANCE IN MEDAN - Putra, Ilham Mirzaya (Universitas Islam Negeri Raden Intan Lampung, 2024)
Setara Institute studied the application of tolerance values in urban Indonesia. This study places Medan in the 10 cities with the lowest tolerance index. One of the indicators is government policy. Therefore, this research aimed to describe: 1) the tolerance policy in Medan City, 2) the realization of the tolerance policy in Medan City, and 3) intolerant events or disturbance of religious/belief harmony in Medan City. The research was conducted with a qualitative-descriptive approach. Interview, observation, and documentation are the data collection techniques used. The informants were selected purposively consisting of the government, FKUB, and PAMK of Medan city. Data analysis was conducted in stages: data reduction, data presentation, and conclusion drawing. To ensure data validity, FGDs, triangulation of sources, techniques, and time were conducted. The results showed that: 1) The Medan City Government's policies in the 2021-2024 period have sufficiently contained aspects of religious tolerance and moderation. 2) Policy realization is carried out regularly and incidentally by the Government and FKUB of Medan city, and 3) There is a decrease in intolerant events or disturbance of KBB in 2021-2022.